What about adaptiveness? The case of organisational resilience and cognition - Secchi, Davide; Neumann, Martin; Festila, Maria S.; Gahrn-Andersen, Rasmus (Frontiers in Complex Systems, 2024)
This paper makes the very simple, perhaps straightforward point that 'adaptiveness' cannot be taken for granted when analysing a complex system. The paradigm of 'Complex Adaptive Systems' (CAS) theory makes it clear that a key feature of complex systems is the ability to adapt to changes in their environment. This is, indeed, relevant to many systems (e.g., living and social systems) since change is embedded in the way in which systems evolve over time. At the same time, adaptiveness is a strong assumption to make, since it prioritises change over stability and it can be a straight jacket, especially when it comes to studying complexity in the context of human social organising. By using a Case Study, this paper highlights the limits of a focus on adaptiveness and pushes for a more "neutral" perspective that allows researchers to appreciate a wider set of mechanisms, norms, and behaviours pertaining to complex social systems.